Answer:
option-A
![\frac{x^4+3x^3-2x^2+4}{x-2}=x^3+5x^2+8x+16+\frac{36}{x-2}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E4%2B3x%5E3-2x%5E2%2B4%7D%7Bx-2%7D%3Dx%5E3%2B5x%5E2%2B8x%2B16%2B%5Cfrac%7B36%7D%7Bx-2%7D)
Step-by-step explanation:
we are given
divisor is
![=x^4+3x^3-2x^2+4](https://tex.z-dn.net/?f=%3Dx%5E4%2B3x%5E3-2x%5E2%2B4)
Dividend is
=x-2
so, we can use synthetic division
so, we can write our expression as
![\frac{x^4+3x^3-2x^2+4}{x-2}=x^3+5x^2+8x+16+\frac{36}{x-2}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E4%2B3x%5E3-2x%5E2%2B4%7D%7Bx-2%7D%3Dx%5E3%2B5x%5E2%2B8x%2B16%2B%5Cfrac%7B36%7D%7Bx-2%7D)
so,
option-A
It is 6, 8, 12 , because you know that the perimeter of the smaller triangle is 13, and those are the midpoints of the larger triangle, so it is like half of the larger triangle. So, it happens that 3+4+6 = 13. So 3*2 , 4*2 , 6*2 will be your answer.
Answer:
2x-4+3x+2=48
5x-2=48
5x=48+2
5x=50
x=10
Step-by-step explanation:
this
The answer is A hope it helps plz mark me a brainlest
I would change the fractions to decimals so that I could see least to greatest.
19/6=3.17
47/14=3.36
83/2=41.5
Least to greatest:
19/6, 47/14, 83/2